“I'm obviously not dying so it's not something I need to sort out today”: Considering hepatitis C treatment in the era of direct acting antivirals - Wright, C.; Cogger, S.; Hsieh, K.; Goutzamanis, S.; Hellard, M.; Higgs, Peter (2018)
Background: People who inject drugs are the group at greatest risk of hepatitis C virus (HCV) infection. The advent of new direct-acting antiviral (DAA) treatment provides opportunities for increased uptake of therapy. Methods: We conducted in-depth interviews with thirty HCV positive participants from the SuperMIX cohort study. Interviews were transcribed, coded, and analysed for emerging themes and similarities between participants. General descriptions and critical interpretation of themes were generated and selective quotes extracted verbatim to best illustrate the critical themes. Results: Participants described their experiences of living with HCV, their knowledge of HCV treatment accessibility, and information on the types of support ain themes: Understanding the need for treatment; Knowledge and framing of treatment access; and Support during treatment. Conclusion: The new, highly effective DAAs for the treatment of HCV are heralded as the potential beginning of HCV elimination, especially in settings where scale up is high. Our data from active PWID show that the availability of DAA medications in and of themselves is likely not to be enough to ensure that PWID will come forward for HCV treatment in sufficient numbers to drive elimination.